Siramesine causes preferential apoptosis of mast cells in skin biopsies from psoriatic lesions. (1st July 2017) - Hagforsen, E.; Lampinen, M.; Paivandy, A.; Weström, S.; Velin, H.; Öberg, S.; Pejler, G.; Rollman, O.
Summary: Background: Skin mast cells are implicated as detrimental effector cells in various inflammatory skin diseases such as contact eczema, atopic dermatitis and psoriasis. Selective reduction of cutaneous mast cells, e.g. by inducing targeted apoptosis, might prove a rational and efficient therapeutic strategy in dermatoses negatively influenced by mast cells. Objectives: The objective of the present study was to evaluate whether a lysosomotropic agent such as siramesine can cause apoptosis of mast cells present in psoriatic lesions. Materials and methods: Punch biopsies were obtained from lesional and uninvolved skin in 25 patients with chronic plaque psoriasis. After incubation with siramesine, the number of tryptase‐positive mast cells and their expression of interleukin (IL)‐6 and IL‐17 was analysed. Skin biopsies were digested to allow flow cytometric analysis of the drug's effect on cutaneous fibroblasts and keratinocytes. Results: Siramesine caused a profound reduction in the total number of mast cells in both lesional and uninvolved psoriatic skin biopsies without affecting the gross morphology of the tissue. The drug reduced the density of IL‐6‐ and IL‐17‐positive mast cells, and showed antiproliferative effects on epidermal keratinocytes but had no apparent cytotoxic effect on keratinocytes or dermal fibroblasts. Conclusions: Considering the pathophysiology of psoriasis, the effects of siramesine on cutaneous mast cells may prove favourable from the therapeutic aspect. The results encourage further studies to assess the usefulness of siramesine and other lysosomotropic agents in the treatment of cutaneous mastocytoses and inflammatory skin diseases aggravated by dermal mast cells.